Crisis communication and crisis management an ethical practice - St. John, Burton 1957-; Pearson, Yvette E. (SAGE Publications, 2017)
Crisis Communication and Crisis Management: An Ethical Approach is the only text on the market to provide students with the integration of ethical inquiry into the fundamentals of crisis communication.. Authors Burton St. John III and Yvette E. Pearson combine comprehensive coverage of the key skills, concepts, and theories of crisis communication with an extensive collection of contemporary case studies, giving students a strong understanding of the essential role that communicators play in moments of crisis. Students are encouraged to build upon their communication and ethical decision making skills using a variety of stakeholder inventories, hypothetical scenarios, discussion questions, and professional profiles. Students will also gain exposure to a mixture of discrete and ongoing crises, preparing them to manage both one-time crises and continuing crises.--Provided by publisher.